Marketing and Advertising- Meaning Creation and its Understanding - Singh , Priyanka; Mishra, Saurabh (International Journal of Psychosocial Rehabilitation, 2020)
Imagine yourself in a communication situation only in a visual format; how will you be able to understand the advertiser’s message? How will you be able to analyze and mention its acceptability in your society? How will the viewers be able to understand the reliability of the shown visual? And what will be the difference if oral communication is added to it? This is what this paper aims to do: construct the pragmatic meaning from something that looks as simple as a photograph and sounds as sweet as a poem. For this unraveling process of meaning, certain signifying practices come into existence.